2017
DOI: 10.1002/nur.21809
|View full text |Cite
|
Sign up to set email alerts
|

Parenting stress and development of late preterm infants at 4 months corrected age

Abstract: Parenting stress has been linked to child development issues in early preterm infants, but less is known about its effects on development in infants born late preterm. We examined relationships between parenting stress of 108 mothers and 108 fathers and development of late preterm infants born at 34 0/7 to 36 6/7 weeks gestation. At 4 months corrected age, mothers and fathers completed the Parenting Stress Index (PSI‐3); mothers were primary caregivers in almost all families and completed the Ages and Stages Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
3
7
0
Order By: Relevance
“…This is consistent with findings from Mughal et al. ( 2017 ). At the same time, parents, as the main support of their children, directly affect the quality of life of the children.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This is consistent with findings from Mughal et al. ( 2017 ). At the same time, parents, as the main support of their children, directly affect the quality of life of the children.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, the findings from the present study indicated parents showed negative emotions such as anxiety and depression when the child was ill. This is consistent with findings from Mughal et al (2017). At the same time, parents, as the main support of their children, directly affect the quality of life of the children.…”
Section: The Traditional Postpartum Practice Of Zuo Yue Zi Presentssupporting
confidence: 92%
See 1 more Smart Citation
“…The study also focused on children who were born preterm (in addition to children born at term) to examine a context in which parenting may be especially challenging, given that preterm children struggle to interact as well as to regulate emotions which can cause parenting stress (e.g. Mughal et al, 2017;Singer et al, 2003). In the search for specific parenting influences, the present study focused on the capacity to mentalize and captured the reflective functioning (RF) score of the parents.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has shown that children born preterm cause parenting stress because they interact less responsively and clearly (e.g. Mughal, Ginn, Magill-Evans, & Benzies, 2017;Singer et al, 2003). Evidently, children born preterm have not yet developed the capacities to form and maintain interactions as well as to regulate emotions (e.g.…”
mentioning
confidence: 99%